INVESTIGATING CULTURABLE GRAM POSITIVE COCCI FROM THE SURFACE OF MOBILE PHONES WITH DIFFERENT FORM FACTORS - Choon, Weng Lee; Pei, Li Heng (Malaysian Journal of Science, 2014)
A total of 99 mobiles phones were grouped according to their form factor that is flip phone and candy bar designs, and their contact surfaces were swabbed and cultured onto both R2A and SPCA media. We usually obtained bacterial abundance between 0 – 50 cfu cm−2 , even though densities up to 490 cfu cm−2 on R2A and 212 cfu cm−2 on SPCA were also recorded. Our study showed that candy bar phones harbored more bacteria, and served as a more important bacterial reservoir as compared to flip phones. Our results also suggested the importance of using mobile phone covers to reduce bacterial abundance. We also found that the Gram positive cocci isolated were similar to the normal flora present on human skin. In this study, more bacterial colonies were consistently found on R2A. R2A was a more suitable isolation medium and performed better for surface microbes. ABSTRAK Sejumlah 99 telefon bimbit telefon telah dikumpulkan mengikut faktor reka bentuk iaitu telefon ‘flip’ dan kandi bar, dan permukaan sentuhan mereka telah dikesat dan dikultur di atas kedua-dua media R2A dan SPCA. Pada kebiasaannya, kepadatan bakteria diperolehi di antara 0 – 50 cfu cm-2 , walaupun kepadatan bakteria sehingga 490 cfu cm-2 pada R2A dan 212 cfu cm-2 pada SPCA juga dicatat. Kajian kami menunjukkan bahawa telefon kandi bar mempunyai lebih bakteria, dan berpotensi sebagai takungan bakteria yang lebih penting berbanding telefon flip. Keputusan kami juga mencadangkan kepentingan menggunakan penutup telefon mudah alih untuk mengurangkan kepadatan bakteria. Kami juga mendapati bahawa Gram positif cocci yang dipencilkan adalah serupa dengan flora normal yang ada pada kulit manusia. Dalam kajian ini, secara konsisten lebih koloni bakteria telah dikultur pada R2A. R2A adalah medium pengasingan yang lebih sesuai dan berprestasi lebih baik untuk mikrob pada habitat permukaan. Keywords: surface bacteria, mobile phones, different form factors, Staphylococcus aureus